2021
DOI: 10.7189/jogh.11.18002
|View full text |Cite
|
Sign up to set email alerts
|

Current levels of coverage of iron and folic acid fortification are insufficient to meet the recommended intake for women of reproductive age in low- and middle-income countries

Abstract: Background Food fortification can be an effective intervention to improve maternal and child health. Folic acid fortification can reduce neural tube defects due to folate deficiency. Iron fortification is effective to reduce maternal anemia due to iron deficiency. The paper describes the methods for estimating current coverage levels for iron fortification and folic acid fortification and estimates current impact of fortification in low- and middle-income countries (LMICs) using the Lives Saved To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Although fortification programs are being introduced in most low and middle-income countries, the impacts of these programs have been restricted either by low levels of fortification in industrialized food, low consumption of fortified food, or both. 165 Folic acid receptors and cancer risk: future prospectives Many types of human cancer, such as BC, ovarian cancer, endometrial cancer, lung cancer, CRC, and cerebral tumors, have shown increased FR expression levels compared with healthy tissues. 166,167 FR can be a target to improve cancer therapy outcomes.…”
Section: Mandatory Fortification Of Folic Acidmentioning
confidence: 99%
“…Although fortification programs are being introduced in most low and middle-income countries, the impacts of these programs have been restricted either by low levels of fortification in industrialized food, low consumption of fortified food, or both. 165 Folic acid receptors and cancer risk: future prospectives Many types of human cancer, such as BC, ovarian cancer, endometrial cancer, lung cancer, CRC, and cerebral tumors, have shown increased FR expression levels compared with healthy tissues. 166,167 FR can be a target to improve cancer therapy outcomes.…”
Section: Mandatory Fortification Of Folic Acidmentioning
confidence: 99%
“…There is a high prevalence in micronutrient malnutrition in (LMICs), after applying large-scale food fortification, major improvements were recorded for multiple diseases, including NTDs prevalence which decreased by 41% after folic acid fortification programs were applied for a mean of 4.2 years (17). In comparison with high-income countries, LMICs may have a folic acid fortification programs, but the desirable benefits have not achieved, one of the main limitations are low awareness and compliance of consumption of folic acid fortified meals among general populations, especially females of childbearing age (18).…”
Section: Food Fortification With Folic Acidmentioning
confidence: 99%
“…Several studies have reported that in vulnerable populations in LMICs, the diets that are both available and affordable are not sufficient to cover nutritional needs of women or children (de Jager et al, 2018; Fahmida et al, 2014; Hlaing et al, 2016; Shi et al, 2010). Fortification programs have shown some successes in improving micronutrient intakes, but several gaps are still to be covered (Castillo‐Lancellotti et al, 2013; Keats et al, 2019; Osendarp et al, 2018; Tong & Walker, 2021). For example, while fortified food has been shown to be major contributor to apparent intakes of vitamin A and iodine in women in four African countries, iron fortification programs appeared to underperform notably due to the low consumption of fortified flour (Friesen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Fortification programs have shown some successes in improving micronutrient intakes, but several gaps are still to be covered (Castillo-Lancellotti et al, 2013;Keats et al, 2019;Osendarp et al, 2018;Tong & Walker, 2021). For example, while fortified food has been shown to be major contributor to apparent intakes of vitamin A and iodine in women in four African countries, iron fortification programs appeared to underperform notably due to the low consumption of fortified flour (Friesen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%